Fusarium spp. and Aspergillus flavus infection induces pathogen-specific and pathogen-independent host immune response in patients with fungal keratitis - Dinesh, Shreya; Prajna, Lalitha; Venkatesh, Prajna Namperumalsamy; Dharmalingam, Kuppamuthu; Devarajan, Bharanidharan (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionFungal keratitis, caused primarily by Fusarium spp. and Aspergillus flavus, is a significant cause of corneal blindness, particularly in tropical regions. Current antifungal agents like natamycin and voriconazole have limited efficacy, underscoring the need for a deeper understanding of host immune responses.MethodsThis study employed high-throughput RNA sequencing to investigate differential gene expression in human corneal tissues from patients with Fusarium spp. and A. flavus keratitis and compared them to control cadaver corneal samples. RNA was extracted from infected and control samples, followed by sequencing and differential expression analysis. Further confirmation of differential expression of selected genes were carried out by Real-Time quantitative PCR (RT-qPCR). ResultsData analysis identified common and Fusarium spp. and A. flavus-specific differentially expressed genes (DEGs). Pathway enrichment analysis using common genes identified pathways enriched in both infections, such as interleukin 17 (IL-17), tumor necrosis factor (TNF), and chemokine signalling. Expression of hub genes, including S100 calcium binding protein A7 (S100A7), S100 calcium binding protein A8 (S100A8), S100 calcium binding protein A9 (S100A9) and C-X-C motif chemokine ligand 8 (CXCL8), identified in interleukin 17 (IL-17) signalling, was confirmed by RT-qPCR analysis. Fusarium spp.-specific DEGs, including complement C3 (C3), interleukin 6 (IL-6), interleukin 19 (IL-19) and leucine rich alpha-2-glycoprotein 1 (LRG1), are enriched in pathways such as positive regulation of immune responses, acute inflammatory responses, leukocyte cell-cell adhesion, and the regulation of cell-cell adhesion. A. flavus-specific DEGs, such as triggering receptor expressed on myeloid cells 2 (TREM2) and apolipoprotein E (APOE), are predominantly enriched in adaptive immune response, negative regulation of immune system process, negative regulation of immune response, cell migration and motility pathways.DiscussionRT-qPCR confirmed the key pathogen-specific DEGs, highlighting their potential as biomarkers for pathogen-specific immune responses. These findings provide insights into the distinct immune pathways triggered by Fusarium spp. and A. flavus, offering new therapeutic targets for improving fungal keratitis treatment.